Raciality, Racism and Emancipation of Afro-descendants in Eastern Cuba. A Look from the Las Tunas Region - Montero Quesada, José Guillermo (2019)
The issue of racialism, racism and racial emancipation around the Afro-descendant population in Cuba has been addressed by several disciplines, especially, history and anthropology. Studies that make it possible to enrich the diversity of views on the subject from a regional perspective are not enough. This article constitutes an approximation to the topic in Las Tunas, a region of eastern Cuba, with the aim of showing its particularities during three major stages: colonial, neocolonial Republic and the so-called Revolution in power. The study is carried out from the review of documentary sources, interviews with key informants, the local press of the time and historical documents. The analysis from the triangulation of sources made it possible to determine the nuances and the magnitude of racism in these historical stages, and the most relevant result consists of revealing specificities of discriminatory codes around black in a regional context.